The role of clemency procedure in reducing competition violations - kardouh, Linda (Journal of Human Sciences, 2020)
The clemency procedure is considered as a tool for detecting the most harmful agreements on the economy. This procedure allows the competition council to grant total or partial exemption from the financial sanction to the institution which contributes to establish the reality of an illegal agreement in which it participated, and provide elements and information to the authorities which it did not have in advance. However, exemptions from penalties that the competition council may grant to the foundation under clemency programs do not guarantee exemption from sanction before the judge.